Next-generation sequencing-based detection of germline L1-mediated transductions - Tica, Jelena; Lee, Eunjung; Untergasser, Andreas; Meiers, Sascha; Garfield, David A.; Gokcumen, Omer; Furlong, Eileen E.M.; Park, Peter J.; Stütz, Adrian M.; Korbel, Jan Oliver (BMC genomics, 2016)
While active LINE-1 (L1) elements possess the ability to mobilize flanking sequences to different genomic loci through a process termed transduction influencing genomic content and structure, an approach for detecting polymorphic germline non-reference transductions in massively-parallel sequencing data has been lacking.